2012
DOI: 10.1590/s1984-29612012000400011
|View full text |Cite
|
Sign up to set email alerts
|

Chemical identification of Tagetes minuta Linnaeus (Asteraceae) essential oil and its acaricidal effect on ticks

Abstract: The control of tick species that affect animal production is vital for the economic welfare of the cattle industry. This study focused on testing the acaricidal activity of the essential oil from the leaves and stems of Tagetes minuta against several Brazilian tick species, including Rhipicephalus (Boophilus) microplus, Rhipicephalus sanguineus, Amblyomma cajennense and Argas miniatus. The chemical composition of the essential oil was determined by chromatography and spectroscopy analyses, which revealed the p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
20
1
4

Year Published

2013
2013
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 50 publications
(31 citation statements)
references
References 21 publications
2
20
1
4
Order By: Relevance
“…In the search for new methods to control these ectoparasites, medicinal plants emerge as a viable and promising alternative, due to the great variability of species, low cost and accessibility in particular regions (Agnolin et al, ). Over the last years, many essential oils and extracts of natural plants have showed promising effects to control R. microplus (Castro et al, ; Garcia et al, ; Singh and Chaturvedi, ).…”
Section: Introductionmentioning
confidence: 99%
“…In the search for new methods to control these ectoparasites, medicinal plants emerge as a viable and promising alternative, due to the great variability of species, low cost and accessibility in particular regions (Agnolin et al, ). Over the last years, many essential oils and extracts of natural plants have showed promising effects to control R. microplus (Castro et al, ; Garcia et al, ; Singh and Chaturvedi, ).…”
Section: Introductionmentioning
confidence: 99%
“…In many countries, Brazil included, the acaricide-resistant tick population has been increasing, to the point that few acaricides have efficacy of more than 75% of the tick population (GRAF et al, 2004;MENDES et al, 2011). On the other hand, the results of certain studies suggest that environmentally friendly acaricides can be obtained from plants (GHOSH et al, 2011;GARCIA et al, 2012). As an alternative, plant extracts are used to manage animal health and parasite control in several regions in the world (GITHIORI et al, 2006;TAMIRU et al, 2013;NYAHANGARE et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…In the last decades, plant extracts were widely used against phytophagus pests and mosquitoes (Balandrin et al, 1995). The effect of neem extract on hard ticks was investigated by Rice, (1993), Magadum et al, 2009, BroglioMicheletti et al, (2010) and Garcia, (2012 and their results revealed a considerable efficacy against ticks.…”
Section: Discussionmentioning
confidence: 99%
“…This result is similar to results obtained by Kaaya and Saxena, (2000) who also found that feeding neem seed powder mixed with rabbit pellets (100:400 g) to goats daily for three weeks completely inhibited attachment and development of B. decoloratus larvae. Also with Garcia, (2012) who recorded 100% efficacy of commercial neem oil (Azadirachta indica) on A. miniatus larvae using the larval packet test (LPT). On contrast, Al-Rajhy et al (2003) concluded that azadirachtin showed some effects on larvae of camel tick, Hyalomma dromedarii.…”
Section: Discussionmentioning
confidence: 99%